Co-infection of tilapia lake virus and Streptococcus agalactiae in red hybrid tilapia [Oreochromis niloticus (Linnaeus, 1758) x O. mossambicus (W.K.H. Peters, 1852) ] - Basri, Lukman (2022)
Tilapia tilapinevirus or known as Tilapia Lake Virus (TiLV) is an emerging virus accountable for a viral disease in cultured and wild tilapia. TiLV has been responsible for a massive mortality of tilapia around the globe including Malaysia. Interestingly, most cases of TiLV-infected fish in Malaysia were co-present with bacterial pathogen including Streptococcus agalactiae that often resulted with a high death rate. The prominence of TiLV and S. agalactiae co-infection has not been explored concerning the interactions and mechanisms of these two infectious agents and their possible impact on the disease in tilapia. Thus, this study was conducted to determine the median lethal dose (LD50), and pathogenicity of TiLV and S. agalactiae single and co-infection in red hybrid tilapia (Oreochromis niloticus × O. mossambicus) following intraperitoneal (IP) injection route. In this study, the red hybrid tilapias were challenged with different concentrations of TiLV (104, 105, and 106 TCID50/mL) and S. agalactiae (103, 104, 105, 106 and 107 CFU/mL). Following the infections, the LD50 of TiLV and S. agalactiae was determined at 106 TCID50/mL and 104 CFU/mL, respectively. The clinical signs, and gross lesions of TiLV and S. agalactiae challenged fish were similar as observed in the naturally infected fish. Then, by referring to the obtained LD50, the fish were challenged with 106 TCID50/mL of TiLV and 103 CFU/mL of S. agalactiae following the single and co-infection studies. The coinfected fish showed a higher cumulative mortality (60.00% in TiLV-S. agalactiae co-infection, and 73.33% in S. agalactiae-TiLV co-infection) compared to the single infected fish (40.00% in TiLV infection, and 20.00% in S. agalactiae infection). Important histopathological findings such as intracytoplasmic inclusion bodies, and syncytial giant cells were also frequently observed in the co-infected fish with some of the lesions were significantly (P < 0.05) severe compared to the single infected fish. The viral and bacterial load recovered from the fish’s brain and liver in qPCR analysis showed a significantly (P < 0.05) higher load pattern was observed in the co-infected fish following the introduction of the second pathogen compared to the single infected fish. The viral particles and bacterial cells were also observed using the TEM analysis and important ultrastructural lesion was found in the infected organs. This study showed the red hybrid tilapia was susceptible to both pathogens following the IP challenge and the co-infection between TiLV and S. agalactiae synergistically worsened the disease severity in tilapia. The results could help in the future effective disease management strategies in cultured tilapia in Malaysia.